From conflict to cohesion: community-based grievance redress in informal settlements regularization projects in emerging urban centers in Tanzania - Mussa S. Muhoja; Regina John Lyakurwa (Cogent Social Sciences)
In many rapidly growing towns across Tanzania, government-led efforts to formalize informal settlements through regularization aim to reduce conflicts and bring order. Yet, these initiatives often expose tensions, especially in areas shaped by overlapping claims, undocumented land histories, and fragile social relationships. This study examines how communities respond when formal land governance encounters these complex realities. Drawing on participant observation, focus group discussions, and interviews with community members, local leaders, and project officials, it highlights the powerful but often overlooked role of community-based grievance redress mechanisms. These forums help rebuild trust, promote fairness, and give people a voice in decisions rooted in lived experience, cultural values, and social ties. As such, they function as everyday courts of justice, grounded in local legitimacy. The study finds these grassroots processes are not peripheral to land reform but essential. They form what this paper calls “infrastructures of trust”: informal networks of fairness, inclusion, and participation that formal institutions struggle to establish. By recognizing the value of community-led dispute resolution, the study shows how these mechanisms improve trust in land governance, strengthen social cohesion, and make regularization more sustainable and inclusive. It calls for a shift in how land governance is understood and practiced.